THE INFLUENCE OF J.-P. SARTRE’S PHILOSOPHY ON THE DEVELOPMENT OF THE ENGLISH EXISTENTIAL NOVEL - АСАДЗАДЕ, Расіма Фархад гизи (Київський національний університет імені Тараса Шевченка, 2022)
The article attempts to study English existentialism in the light of J.-P. Sartre's philosophy. J.-P. Sartre is considered a theorist of existentialism as a literary trend. Existential motives characteristic of the 20th century European literature are used in the works of the prominent representatives of the English literature, such as A. Murdoch, W. Golding, C. Wilson, and M. Spark. Existentialism as a philosophical trend has played an important role in finding a way out of crisis and forming a new social worldview. English existentialist writers broke the norms of the view on human relations with society. In their works they focused on the concept of man, their essence and inner world, determined their place, both in philosophy and in literature. The named scholars showed that history brings to the political forefront a person who is doomed to freedom with their whole being and repeatedly transgresses various forms of social existence. This is also the main philosophical platform of the European existential literature. Through the prism of accepting such a position, the main credo of Sartre’s entire life activity is justified: realizing and justifying his spiritual, moral and value choice, a person thereby assumes responsibility for the fate of the whole world. Sartre’s main works turned out to be free from serious shortcomings. On the contrary, the synthesis of democratic and individualistic tendencies appeared complex, contradictory, and therefore gave rise to further discussions in the world literature. However, the main theoretical positions of the thinker had a significant impact on the existential literature of Europe, in particular, on the English literature.

У статті пропонується дослідження впливу філософії Ж.-П. Сартра на розвиток англійського екзистенційного роману. Ж.-П. Сартр вважається теоретиком екзистенціалізму як літературного напряму. У творах яскравих представників англійської літератури А. Мердок, В. Ґолдінґа, К. Вілсона, М. Спарк використовуються екзистенційні мотиви, характерні для всієї європейської літератури XX століття. Екзистенціалізм як філософський напрям мав важливе значення в пошуку виходу з кризових ситуацій та формуванні нового суспільного світогляду. Англійські письменники-екзистенціалісти руйнували звичні норми світобачення зв’язків людини із суспільством. Вони приділяли у своїх творах основну увагу людині, її сутності та внутрішньому світу, визначали її місце як у філософії, так і в літературі. У працях названих постатей докладно показано, що історія висуває на політичну авансцену людину, яка всім своїм єством приречена до свободи і неодноразово порушує різноманітні форми соціального буття. Відповідну філософську платформу європейської екзистенційної літератури вважаємо освновною, крізь призму прийняття якої обґрунтовується головне кредо всієї життєдіяльності Сартра: усвідомлюючи і виправдовуючи свій духовно-моральний і ціннісний вибір, людина таким чином бере на себе відповідальність за долі всього світу. В основних працях Сартра важко помітити серйозні недоліки. Навпаки, синтез демократичних та індивідуалістичних тенденцій виявився складним, суперечливим, а тому зумовив подальші дискусії у світовій літературі. Проте основні теоретичні положення мислителя суттєво вплинули на екзистенційну літературу Європи, зокрема й на англійський роман.
ВПЛИВ ФІЛОСОФІЇ Ж.-П. САРТРА НА РОЗВИТОК АНГЛІЙСЬКОГО ЕКЗИСТЕНЦІЙНОГО РОМАНУ
Keywords: філософія; екзистенціалізм; творчість; особистість; англійська література; роман; Ж.-П. Сартр; philosophy; existentialism; creativity; personality; English literature; novel; J.-P. Sartre